Power-switching converters - Ang, Simon S., 1957-; Oliva, Alejandro (Boca Raton, Fl. : CRC Press, 2011)
'Significantly expanded and updated with extensive revisions, new material, and a new chapter on emerging applications of switching converters, Power-Switching Converters, Third Edition offers the same trusted, accessible, and comprehensive information as its bestselling predecessors. Similar to the two previous editions, this book can be used for an introductory as well as a more advanced course.Chapters begin with an introduction to switching converters and basic switching converter topologies. Entry level chapters continue with a discussion of resonant converters, isolated switching converters, and the control schemes of switching converters. Skipping to chapters 10 and 11, the subject matter involves an examination of interleaved converters and switched capacitor converters to round out and complete the overview of switching converter topologies.More detailed chapters include the continuous time-modeling and discrete-time modeling of switching converters as well as analog control and digital control. Advanced material covers tools for the simulation of switching converters (including both PSpice and Matlab simulations) and the basic concepts necessary to understand various actual and emerging applications for switching converters, such as power factor correction, LED drivers, low-noise converters, and switching converters topologies for solar and fuel cells. The final chapter contains several complete design examples, including experimental designs that may be used as technical references or for class laboratory projects. Supplementary information is available at crcpress.com including slides, PSpice examples (designed to run on the OrCAD 9.2 student version and PSIM software) and MATLAB scripts.Continuing the august tradition of its predecessors, Power-Switching Converters, Third Edition provides introductory and advanced information on all aspects of power switching converters to give students the solid foundation and applicable knowledge required to advance in this growing field'--
'Many advances have emerged since the second edition. This third edition includes a brand-new chapter on and addresses new subjects, including LED drivers, and DC-DC converters both for solar panels and for fuel cells. This book covers converter power management, phase-shift PWM, and low-noise and bidirectional DC-DC converters, featuring a non-linear discrete model of the DC-DC converter itself. The text discusses new simulation tools such as PSIM, LTSPICE, and POWERESIM, and provides additional and updated information on digital control of DC-DC converters, switched capacitor converters, and power factor controllers'--
Pameran Fakulti/Nijuyon/ Dr. Sallehuddin Mohamed Haris
Includes bibliographical references (p. 599-611) and index.